Implementation of Cyber Notary as a Notary Transformation in the Digital Economy Era (Comparative Study of German Notary Law) - Handayani, Umi; Sulistiyono, Adi; Tejomurti, Kukuh (Jurnal Daulat Hukum, 2025)
The process of implementing the Cyber Notary concept in Indonesia still faces various obstacles due to the provisions in Law No. 2 of 2014 concerning Amendments to Law No. 30 of 2004 concerning the Position of Notary or abbreviated as UUJN which still applies the principle of " Tabellionis Officium Fideliter Exerbo" and several articles in the UUJN which are still traditional. This article analyzes the opportunities and obstacles to implementing Cyber Notary in the Indonesian legal system in facing the Digital Economy era, and elaborates on the best practices of German notary law which has previously implemented the Cyber Notary concept. This article is a legal research with a socio-legal approach, namely that which is related to law and technology and a comparison of notary law with Germany. The results of this study are that there are still several regulations that hinder the entry of the Cyber Notary concept in Indonesia so that changes are needed to the UUJN and the formation of other regulations that support this concept, but on the other hand there is an opportunity for the Cyber Notary concept to be implemented, as stated in the explanation of Article 15 number (3) of the UUJN which is the entry point for the Cyber Notary concept. In order to make changes to the UUJN, Indonesia can make Germany a rule model because it has previously implemented the Cyber Notary concept and has succeeded in integrating digital technology into Notary practices, such as the use of digital signatures, the use of video conferencing and the storage of electronic document archives.